Urine levels of luteinizing hormone as predictor of the period of ovulation for advantage of timed‐artificial insemination in murrah buffalo (Bubalus bubalis). (7th February 2017) - Selvam, RM; Singh, D; Akbarsha, MA; Archunan, G
Contents: Assessment of urine levels of luteinizing hormone (LH) for predicting the reproductive status of animals is in practice. The aim of this study was to predict the period of ovulation based on the urine levels of LH for timed‐artificial insemination to increase the conception rate in buffaloes, which are naturally silent‐oestrous animals. Level of LH in urine was assessed using ELISA, and a cut‐off LH concentration for prediction of ovulation period was obtained using receiver operating characteristic analysis. Artificial insemination was performed before‐ and after ‐positive prediction of ovulation period adopting this method, and the rates of conception were assessed. Urine LH level of 105 mIU/ml ( n = 14) was derived as a cut‐off concentration which predicts the ovulation period. The buffaloes in the positively predicted group (day 1 or 2) inseminated via intracervical route had an increase in the conception rate (83.33%); however, the insemination in the before‐positive‐prediction group resulted in poor conception rates (day 0; 16.66%) compared to that of the naturally inseminated group (day 0; 75.0%). In conclusion, the urinary LH would possibly be a fairly reliable predictor of the ovulation period. The day when cut‐off LH concentration is obtained may be taken as the most favourable time for artificial insemination, so as to attain a much better rate of conception in the buffalo.